A new species of Punctularia (Punctulariaceae, Basidiomycota) from southwest China - Guan, Qian-Xin; Zhao, Wei; Zhao, Chang-Lin (Phytotaxa, 2021)
A new wood-rotting fungal species, Punctularia bambusicola, is proposed based on a combination of morphological features and molecular data. The species is characterized by resupinate, lilac to purple basidiomata, pink to rose tuberculate hymenial surface, monomitic hyphal system with clamped generative hyphae, yellowish to brown dendrohyphidia and ellipsoid basidiospores measuring 6.5–8.5 × 3.5–5 µm. Phylogenetic analyses of combining ITS and LSU nrRNA gene regions demonstrated that P. bambusicola forms a single lineage sister to P. atropurpurascens with strong statistical supports (100% BS, 100% BT, 1.00 BPP).